The Contribution of Self-Efficacy and Family Support to Career Perceptions among Vocational Students in Computer and Network Engineering - Rini Afriany Harahap; Lativa Mursyida; Efrizon Efrizon; Mahesi Agni Zaus (Universitas Negeri Padang, 2025)
Career decision-making during high school is a critical developmental stage in which students begin to define their future professional trajectories. However, many students—particularly by Grade XII—still struggle with identifying a clear career direction. This study investigates the contribution of two key psychological and social factors: self-efficacy and family support, in shaping students' career perceptions. A mixed-methods approach was employed, combining quantitative analysis of 66 students in the Computer and Network Engineering department at SMKN 1 Bukit Tinggi with qualitative data from in-depth interviews. The quantitative findings revealed that self-efficacy and family support significantly influence career perception, contributing a combined variance of 59.2%, with self-efficacy contributing 52.27% and family support 19.44%. Qualitative results corroborated these findings, showing that students with high self-confidence and strong parental involvement demonstrated greater clarity in their career planning. These results highlight the importance of fostering both internal motivation and supportive external environments in preparing students for career decision-making. The study provides empirical evidence for the integration of psychological empowerment and family-based interventions within vocational education frameworks.